Production Performance and Rumen Fermentation of Male Ettawah Crossbred Silage Supplemented with Tannins - Wulandari, Suci; Ningsih, Niati; Yulinarsari, Alditya Putri; Muhamad, Nur; Kusuma, Satria Budi; Bahariawan, Amal (Jurnal Ilmu-Ilmu Peternakan, 2024)
The purpose of this study was to examine the effects of adding tannins to silage feed on the performance of male dairy goats. The benefits of this research are that it is useful for application to other ruminant livestock for obtaining preserved feed but with nutritional qualities that can still be maintained. The research consisted of 2 treatments. Each treatment consisted of 4 male Etawa crossbred goats (ECG) as well as replications. Treatment T0 was used for the group of goats fed complete silage without the addition of tannins, while T1 was used for the group of goats fed complete silage with the addition of tannins. The parameters observed for production performance were consumption (DM, CP, TDN), daily weight gain (DWG), and feed conversion ratio (FCR). The parameters observed for rumen metabolism were rumen fluid pH, partial VFA, and ammonia (NH3). The data obtained were explained nonparametrically using the Mann?Whitney test by IBM SPSS Statistics 24. The results showed that complete silage feed supplemented with tannin (9 g/kg fresh feed) contained more crude protein than that without tannin. The effect on the production performance of male Etawa crossbred goats (ECG) was better for DWG, namely, 87.0 g/head/day, than for those without additional tannins, namely, only 53.3 g/head/day. Providing tannin to complete silage feed also improved the C2:C3 ratio in the rumen metabolic system, as indicated by an increase in the efficiency of energy use, which is beneficial for the growth phase of livestock.